Other renaissances : a new approach to world literature - Schildgen, Brenda Deen, 1942-; Zhou, Gang, 1966-; Gilman, Sander L. (Palgrave Macmillan, 2006)
Other Renaissances is a collection of twelve essays discussing renaissances beyond the fifteenth- and sixteenth-century Italian and then pan-European Renaissance. With a prologue by Giuseppe Mazzotta about the Italian Renaissance as a?world-making? epistemology, and an afterward by Sander Gilman to summarize the cogent points of the essays, the collection proposes an approach to reframing the Renaissance in which the European Renaissance becomes an imaginative idea, rather than a particular moment in time. Essays cover the Chinese, Harlem, Bengali, Tamil, Maori, Irish, Mexican, Arab, Hebrew, and Cold War Renaissance of the US in the 1950s.